2010
DOI: 10.1051/forest/2009083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stand density on ecosystem properties of subalpine forests in the southern Rocky Mountains, USA

Abstract: Abstract• Mixed coniferous, subalpine forest communities in the Rocky Mountains are historically dense and have experienced infrequent, high-severity fire. However, many of these high-elevation stands are thinned for a number of perceived benefits.• We explored the effects of forest stand density on ecosystem properties in subalpine forests in Colorado, USA, 17-18 y after forests were managed for timber.• Forest structure significantly altered the composition and chemical signature of plant communities. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…). It was, however, consistent with the increase of Pinus flexilis green leaf phenolics : N ratio in response to thinning observed by Hall and Marchand () in a coniferous subalpine forest ecosystem. These response patterns were generally consistent over a large scale and between humus types, highlighting that they were largely independent of soil fertility context in a range of acidic forest soils and could potentially be generalizable to a broad set of temperate forest ecosystems dominated by tree species with ecological features similar to Q. petraea (Symstad et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…). It was, however, consistent with the increase of Pinus flexilis green leaf phenolics : N ratio in response to thinning observed by Hall and Marchand () in a coniferous subalpine forest ecosystem. These response patterns were generally consistent over a large scale and between humus types, highlighting that they were largely independent of soil fertility context in a range of acidic forest soils and could potentially be generalizable to a broad set of temperate forest ecosystems dominated by tree species with ecological features similar to Q. petraea (Symstad et al.…”
Section: Discussionsupporting
confidence: 90%
“…Further, many species favored by tree removal, such as various grass species and the fern P. aquilinum, have been reported to produce poorly decomposable leaf litter (Cornwell et al 2008). Hall and Marchand (2010) also found that tree removal increased the green leaf phenolic : N ratio of several common understory plants species, thus likely decreasing their leaf litter decomposability. Tree removal thus likely results in a shift toward less decomposable leaf litter of understory plants at the community level in relation to both species turnover and plasticity.…”
Section: Analysis Step and Candidate Path Models Explanationmentioning
confidence: 81%
See 1 more Smart Citation
“…In stands that are not regulated through management, the stem densities are higher, the competition for water thus more intense and this increases the effect of climate change on competition. However, Douglas-fir stands are managed for wood production and show a structure and a biogeochemistry distinct from unmanaged stands (Hall and Marchand, 2010) and since we were interested in the response of managed forests to climate change, we only considered managed stands.…”
Section: Further Effects Under Changing Climatementioning
confidence: 99%
“…This study employs a retrospective approach to understand the question of multi-decadal carbon accumulation in riparian restoration treatments. While retrospective studies may lack consistency in size or type of treatment, they are often used in managed landscapes to assess temporal changes in long-term processes with greater power and cost-effectiveness than can be achieved through short-term experimentation [26][27][28]. We examined patterns of carbon sequestration in biomass and soil resulting from riparian restoration in 42 stream reaches in northern California (Fig.…”
Section: Study Areamentioning
confidence: 99%